Determining the rational areas in the UK meat supply chain for introducing biosensors - Abazari,Sara (2016)
Despite the importance of the UK in meat production in the EU and its increasing population, there is still a lack of rapid, accurate and inexpensive technique to determine an appropriate durability for meat products. As the population increases, the demand for safe and of satisfactory food by both consumers and government raises, so as the demand for a favourable tool to ensure the safety of food products. The operators tend to apply minimum durability for long-life products to avoid risks, which results in the waste of perfectly fine food by both consumers and operators as well as a profit loss for the businesses. Meat production together with wastage cause a great impact on the environment. Further, foodborne diseases have become a significant health problem, affecting the economy of the UK as well as the individuals. Therefore, there has been an increased demand for a tool that rapidly detects the quality of meat and reduce the risk of foodborne diseases. To address these problems, this thesis study aims to determine where in the UK meat supply chain there is a rationale to introduce the target biosensor. To fulfil the purpose, a qualitative research approach was employed, thirty-one interviews were conducted with twenty-two participants from the business operators as well as experts and knowledgeable individuals in the meat industry. To facilitate data analysis, criteria expiry date and/or laboratory testing, interest and finally retail-ready-products were used. The result indicates that there is a rationale to introduce the biosensor to manufacturers, retailers and packers as these operators deal with setting expiry dates and retail packaging. Manufacturers and retailers carry out expensive and time-consuming laboratory testing to both set appropriate durability and reassure the safety of products. This imposes huge costs on the operators, which can be optimised by the use of the biosensor. In assessing the operators interest, manufacturers showed high interest in the use of the target biosensor whilst retailers showed relatively low or no interest. Packers interest however, remain unknown due to the prevention of these operators in participating in this research. As the packaging area in this study was not addressed, conducting a research to discover the interest of packers in the use of biosensors would be interesting. It would also be interesting to identify the choices and techniques deployed by these operators to determine the expiry date of retail-ready-products.
Keywords: Keywords: Biosensors; shelf life; meats; supply chain; retail-ready-products